2010
DOI: 10.4028/www.scientific.net/msf.638-642.781
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and Mechanical Properties of Cr-Al-B-N Coatings Prepared by Reactive D.C. and R.F. Co-Sputtering

Abstract: The current study was undertaken to investigate the synthesis of CrAlN/BN composite coatings having super high hardness by a reactive co-sputtering using CrAl alloy and BN targets and gaseous mixture of Ar+N2, in order to eliminate the possible formation of boride bonding. CrAlN or BN phase was deposited by pulsed d.c.- and r.f.- sputtering, respectively. Plastic hardness, Hpl, and Young’s modulus, E*, of the coatings increased with BN phase ratio, reaching a maximum value of ~46 GPa and 390 GPa at ~8 vol. %… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Many authors indicated that even a small addition of another element to the coating significantly affects the size of the crystallites. Nose et al found that an increase in the concentration of boron in the AlCrN coating causes a reduction of crystallites oriented in the (111) plane from about 23 nm to about 10 nm and in the (200) plane from about 12 nm to about 5 nm [ 39 ]. Tritremmel et al confirmed the decrease in the crystallite size from about 35 nm to about 6 nm in AlCrSiN coatings produced by cathodic arc evaporation from AlCrSi cathodes, in which Al/Cr = 1 and the silicon concentrations from 0 to 20 at% [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many authors indicated that even a small addition of another element to the coating significantly affects the size of the crystallites. Nose et al found that an increase in the concentration of boron in the AlCrN coating causes a reduction of crystallites oriented in the (111) plane from about 23 nm to about 10 nm and in the (200) plane from about 12 nm to about 5 nm [ 39 ]. Tritremmel et al confirmed the decrease in the crystallite size from about 35 nm to about 6 nm in AlCrSiN coatings produced by cathodic arc evaporation from AlCrSi cathodes, in which Al/Cr = 1 and the silicon concentrations from 0 to 20 at% [ 11 ].…”
Section: Discussionmentioning
confidence: 99%